Performance Evaluation of a Radio-Based Emergency Communication System for Mountain Hiking Applications - Anggraini, Elsa; Simarmata, Togi; Rayesa, Mohammad; Fikri, Muhammad; Fatih, Muhammad (Lembaga Pengembangan Kinerja Dosen, 2026)
Reliable communication is essential for mountain hiking activities, particularly in emergency situations where cellular networks are often unavailable. This study evaluates the performance of a radio-based emergency communication system designed to transmit GPS location data from multiple transmitter nodes to a single receiver using a multipoint-to-point communication scheme. The main contribution of this work is the field-based evaluation of a practical communication system capable of delivering location information from multiple users in mountainous environments without relying on cellular infrastructure. Field experiments were conducted using handheld radios operating in the 400–470 MHz frequency band under both line-of-sight (LOS) and non-line-of-sight (NLOS) conditions. The results show that the system achieved maximum communication distances of 834.40 m and 648.03 m under LOS conditions, while NLOS communication was maintained up to 279.00 m and 277.18 m. In addition, the transmitted GPS coordinates were successfully received and displayed at the monitoring station with positional differences of only a few meters compared to a reference GPS application. These results demonstrate that the proposed system can provide a practical and reliable solution for emergency communication and location monitoring in mountainous environments.